Increasing Student Learning Outcomes in Mathematics About Operational Numbers With Role Playing Method of Colors Media in Class V SDN Karanganyar Gunung 02 Semarang - Khasanah, Siti Khuluqul (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to improve the ability to learn mathematics through the media of colored marbles in fifth grade students of SD Karang Anyar Gunung 02 Candisari District, Semarang City. This study uses the Kemmis Taggart class action research method with the stages of planning, implementing, observing and reflecting which consists of two cycles. The subjects of this study were 24 students of class V. Data collection techniques used observation, interviews and documentation. Techniques of data analysis using qualitative analysis. The results of the study showed that out of the 24 students who had completed the pre-cycle, only 11 (45%) students and 13 (55%) students had not completed. In the first cycle showed an increase, namely students who completed there were 16 students or (66.67%) and students who had not completed there were 8 students or (33.33%), then the results of the improvement in learning cycle II showed an increase, namely students who completed learning there were 23 students or (96%) and students who have not finished studying there is 1 student or (4%). Thus the results of the color marbles media method can improve the learning outcomes of fifth grade students at SDN Karanganyar Gunung 02 Semarang in the 2019/2020 academic year.